A note on generalized convex functions - Zaheer Ullah, Syed; Adil Khan, Muhammad; Chu, Yu-Ming (Journal of inequalities and applications, 2019)
In the article, we provide an example for a η -convex function defined on rectangle is not convex, prove that every η -convex function defined on rectangle is coordinate η -convex and its converse is not true in general, define the coordinate ( η 1 , η 2 ) -convex function and establish its Hermite–Hadamard type inequality.